Immunobiology : the immune system in health and disease - Janeway, Charles (Churchill Livingstone, 2001)
Immunobiology tells the story of the immune system. The book covers all of the material that comprises a typical immunology course. The Fifth Edition is an extensive revision which includes new material and major insights, improved logical progression of topics, and an emphasis on unifying principles. With clear, concise text and a full-color art program, this book continues to set the standard for a current and authoritative immunology textbook.
Keywords: Biology; biologie; imunita; imunitní systém; Biologie; Immunotherapy; imunoterapie; Imunoterapie; Immunity; Immune System; alergologie a imunologie